FAMILY INSTITUTE TRANSFORMATION IN RUSSIAN SOCIETY: SOCIAL CONTRADICTIONS AND SOCIOLOGICAL ILLUSIONS - Nikita A. Vyalykh (Векторы благополучия: экономика и социум, 2021)
The relevance of the article is determined by the need to overcome the existing differences in understanding the social essence of the family institute transformation in Russian sociology today. The aim of the article is a revision of research practices of analysis of structural, value and role dimensions of marriage and family relations. The novelty of the work is in identifying the common illusions and contradictions, typical for the sociological research methodology of marriage and family relations. The paper consists of two main parts. In the first part the basic trends in marriage and family sphere transformation are revealed. Currently, there is a tendency to overcome the cognitive one-sidedness of evolution and crisis paradigms in an attempt to determine a vector of social changes in family behavior in Russian society. The second part deals with sociological type of thinking in the field of family studies. It is showed that the family representation as a cell of the institutional matrix is a methodological necessity but not objective reality. A special attention is given to the cognitive attitude of many scientists to social criticism of governmental family policy in Russia. The author comes to the conclusion about the importance of personal responsibility role increase in the sphere of family institute well-being and social health in modern Russian society.